Interdecadal Pacific Oscillation Drives Enhanced Greenland Surface Temperature Variability During the Last Glacial Maximum - Song, Zhaoyang; Latif, Mojib; Park, Wonsun; Zhang, Yuming (Geophysical Research Letters, 2021)
Stable oxygen isotope records from central Greenland suggest disproportionally large long ‐ term surface air temperature (SAT) variability during the Last Glacial Maximum (LGM) relative to preindustrial times. Large perturbations in mean atmospheric circulation and its variability forced by extensive Northern Hemisphere ice sheet coverage have been suggested as cause for the enhanced Greenland SAT variability. Here, we assess the factors driving Greenland SAT variability during the LGM by means of dedicated climate model simulations and ﬁ nd remote forcing from the Paci ﬁ c of critical importance. Atmospheric teleconnections from the Interdecadal Paci ﬁ c Oscillation (IPO), a multidecadal oscillation of sea surface temperature in the Paci ﬁ c Ocean, strongly intensify under LGM conditions, driving enhanced surface wind variability over Greenland, which in turn ampli ﬁ es SAT variability by anomalous atmospheric heat transport. A major role of the IPO in forcing Greenland SAT variability also is supported by a number of models from the Paleoclimate Modeling Intercomparison Project Phase III.